PELATIHAN PEMBUATAN BAHAN AJAR BERBASIS TEKNOLOGI INFORMASI DENGAN CAMTASIA STUDIO BAGI GURU DI SMK MUHAMMADIYAH 2 MUNTILAN - MAGELANG - Sholeh, Muhammad; Suraya, Suraya; Suraya, Ign. (UNIVERSITAS PGRI MADIUN, 2018)
Abstract. Teaching materials as one of the media that teachers can use to explain the material to the students. In the era of the development of information technology today, teachers must develop teaching materials that utilize information technology. With the support of information technology, materials or teaching materials that are packaged can be displayed more interesting and interactive. Many applications that teachers can use in creating teaching materials. One of them is Camtasia Studies. With this application, teachers do not need a programming understanding in the development of teaching materials. This application developed video-based and can be equipped with more attractive appearance. As an effort to improve the role of teachers in developing teaching materials, in SMK Muhammadiyah 2 Muntilan has been held training to create teaching materials with Camtasia Studio application. Theresults of training to produce teaching materials and ready to be given to students either through flash disk or uploaded in elearning school. Abstrak. Bahan ajar sebagai salah satu media yang dapat digunakan guru untuk menjelaskan materi kepada para siswa. Di era perkembangan teknologi informasi saat ini, guru harus mengembangkan bahan ajar yang memanfaatkan teknologi informasi. Dengan dukungan teknologi informasi, materi atau bahanajar yang dikemas dapat ditampilkan lebih menarik dan interaktif. Banyak aplikasi yang dapat digunakan guru dalam membuat bahan ajar. Salah satu nya adalah Camtasia Studi. Dengan aplikasi ini, guru tidak memerlukan pemahaman pemrograman dalam pengembangan kan bahan ajar. Aplikasi ini dikembangkanberbasis video dan dapat dilengkapi dengan tampilan-tampilan yang lebih menarik. Sebagai upaya meningkatkan peran guru dalam mengembangkan bahan ajar, di SMK Muhammadiyah 2 Muntilan telah diselenggarakan pelatihan membuat bahan ajar dengan aplikasi Camtasia Studio. Hasil pelatihan menghasilkan bahan ajar dan siap untuk diberikan ke siswa baik melalui flash disk maupun di unggah di elearning sekolah.